Advances in molecular and cell biology. - Bittar, E. Edward (Advances in molecular and cell biology ;, 1993)
Studies on the components of the extracellular matrix have expanded recently and greatly increased our understanding of their biological functions and roles in development and in disease. Because so many new areas have been defined, selection of chapter topics was difficult to limit. Areas with recent developments in both basic knowledge and diseased states have been emphasized. Some of the chapters detail evolving frontiers which are of intense interest, but complete information is not known. For example, several bone morphogenetic factors have been described and others likely exist. The structures of these multifunctional proteins are determined and they appear related. The description of extracellular matrix component receptors is far from complete, but worthy of a progress report since much is already known. Of particular interest is the "promiscuity" of some of these receptors in their interaction with more than one matrix protein and even different ligand specificities on different cell types. Such variability these interactions challenges conventional ideas on the specificity of ligand-receptor interactions. The collagens were traditionally thought of as structural molecules but now have been found to be biologically active. The number of genetically distinct collagen genes is greater than 27 (still increasing!) and their gene regulation is unique. The demonstration of a bi-directional promoter for the collagen IV chains has stimulated research on gene regulation and the DNA binding proteins. A number of diseases have also been shown recently to involve collagens. The proteoglycans have been thought of as largely carbohydrate-containing molecules with the research emphasis placed on the sugars. With the recent DNA sequencing of several protein cores, these molecules have been found to be of tremendous interest. The basement membrane heparan sulfate proteoglycan contains domains with homologies to laminin, immunoglobulin, and LDL. Proteoglycans have multiple activities and function as adhesion factors, cellular receptors, growth factor binding sites, etc. Several chapters are devoted to whole basement membrane and to other matrix components such as fibronectin, thrombospondin, laminin, collagen IV, entactin/nidogen, and elastin which have been shown to have remarkable effect on normal and malignant cell behavior. The structures of these matrix components have been described, and now active sites as well as alternate forms are being defined. The role in tumor growth and acquired and genetic diseases is also reviewed. The potential clinical use of the molecules or active sites is only briefly mentioned but likely to be important in the future